Isolation and Characterization of vB_kpnM_17-11, a Novel Phage Efficient Against Carbapenem-Resistant Klebsiella pneumoniae - Bai, Jiawei; Zhang, Feiyang; Liang, Shuang; Chen, Qiao; Wang, Wei; Wang, Ying; Martín-Rodríguez, Alberto J.; Sjöling, Åsa; Hu, Renjing; Zhou, Yingshun (Frontiers in Cellular and Infection Microbiology, 2022)
Phages and phage-encoded proteins exhibit promising prospects in the treatment of Carbapenem-Resistant Klebsiella pneumoniae (CRKP) infections. In this study, a novel Klebsiella pneumoniae (K. pneumoniae) phage vB_kpnM_17-11 was isolated and identified by using the CRKP as the host. vB_kpnM_17-11 has an icosahedral head and a retractable tail. The latent and exponential phases were 30 and 60 minutes, the burst size of 31.7 PFU/cell and the optimal MOI of 0.001. vB_kpnM_17-11 remain stable at pH values (4-8) and temperature (4-40°C). The genome of vB_kpnM_17-11 is 165,894 bp, double-stranded DNA (dsDNA), containing 275 Open Reading Frames (ORFs). Belongs to the family of Myoviridae, order Caudovirales, and has a close evolutionary relationship with Klebsiella phage PKO111. Sequence analysis shown that the 4530 bp orf022 of vB_kpnM_17-11 encode the depolymerase and had most similarity (85.97%) with L-shaped tail fiber protein of Klebsiella Phage vB_KpnM_311F at amino-acid level. The bacteriostatic efficiency of vB_kpnM_17-11 in vitro was 99.99%. In mouse model, phage administration improved survival and reduced the number of K. pneumoniae in the abdominal cavity by 104-fold. Conclusion, vB_kpnM_17-11 shows excellent in vitro and in vivo performance against K. pneumoniae infection and constitutes a promising candidate for the development of phage therapy against CRKP.